2009
DOI: 10.1097/tp.0b013e3181957308
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Possess Monocyte-like Antigen-presenting and T-cell-Co-stimulatory Capacity

Abstract: Although EPC exhibit endothelial-like surface markers, functional characteristics place these cells in a monocytic lineage. EPC also display antigen-presenting capacity similar to monocytes and much stronger than human vascular EC. Significant T-cell-activating potential will have to be expected from EPC when potentially used therapeutically, especially in allogenic transplant settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Bone marrow-derived progenitor cells are also reported to favor the formation of premetastatic niches, which precondition the environment to facilitate the implantation of tumor cells and the consecutive recruitment of other progenitor cells to promote the neovascularization of metastases (6)(7). More recently, EPCs were documented to act as antigen-presenting cells similar to monocytes (9,10), confirming previous reports identifying populations of EPCs with an intermediate phenotype expressing both endothelial and monocytic/macrophagic properties (11,12).…”
Section: Introductionsupporting
confidence: 67%
“…Bone marrow-derived progenitor cells are also reported to favor the formation of premetastatic niches, which precondition the environment to facilitate the implantation of tumor cells and the consecutive recruitment of other progenitor cells to promote the neovascularization of metastases (6)(7). More recently, EPCs were documented to act as antigen-presenting cells similar to monocytes (9,10), confirming previous reports identifying populations of EPCs with an intermediate phenotype expressing both endothelial and monocytic/macrophagic properties (11,12).…”
Section: Introductionsupporting
confidence: 67%
“…Migration and adhesion are two important steps in EPC homing. Several reports showed that EPCs expressed the Pselectin glycoprotein ligand-1 (PGSL-1), the ligand of P/E selectin, and adhesion molecules on ischemic ECs would have an important role in recruiting circulating EPCs to the murine vasculature (Raemer et al, 2009). In the present study, we observed that endothelial cells in ischemic tissue …”
Section: Discussionsupporting
confidence: 65%
“…1G, H). Adhesion and migration were very important steps in EPC homing to impaired tissues; the expression of P-selectin glycoprotein ligand-1 (PGSL-1), a ligand of P/E selectin, on EPCs has been previously reported (Urao et al, 2008;Raemer et al, 2009). To investigate the effect of apo (a) on EPC adhesion, we treated EPCs with 0.2, 1, 5, 10, 15 mg/mL apo (a) and adopted an RT-PCR method to detect P/E-selectin expressed in the ECs of ischemic tissues, which could promote adhesion of circular EPCs to the endothelium of injured tissues.…”
Section: Apo (A) Attenuated Epcs Adhesion and Migrationmentioning
confidence: 99%
“…Thus, the emerging consensus is that EPCs identified with cell surface markers CD34 and VEGFR2 contain very few, if any, genuine EC progenitors, and are more accurately described as angiogenic macrophages. Three recent papers have further strengthened this view (7375). However, another study has most comprehensively demonstrated that so-called EPCs are predominantly of monocytic lineage (76).…”
Section: Endothelial Progenitor Cells (Epcs)mentioning
confidence: 91%